2012
DOI: 10.1149/2.050208jes
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Soft Carbon and Propylene Carbonate-Based Electrolytes in Lithium-Ion Capacitors

Abstract: The combined use of soft carbon (PeC) as anodic material, and propylene carbonate (PC) as electrolyte solvent is a promising strategy for the realization of high performance lithium-ion capacitors (LIC). PeC electrodes display a capacity of around 80 mAhg −1 during cycling carried out at 5C, which can be maintained for more than 10,000 cycles. This performance is higher than that displayed by most of the carbonaceous electrodes so far proposed for LIC. PC is known to be a safer electrolyte compared to mixtures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 32 publications
(52 reference statements)
0
52
0
Order By: Relevance
“…The specific capacitance obtained for the CDC in this study, 120 F g À1 , is appreciable, yet similar to the values reported for other carbon materials as well. The specific capacitance values of activated carbon in lithium-containing electrolytes reported by other authors range from 60 to 165 F g À1 [8,17,21,22,28,39]. For example, Krause et al [39] obtained a specific capacitance of approximately 110 F g À1 for their carbon black electrodes in a LIC with a LiFePO 4 positive electrode.…”
Section: Comparison Of the Different Lic Cell Typesmentioning
confidence: 96%
“…The specific capacitance obtained for the CDC in this study, 120 F g À1 , is appreciable, yet similar to the values reported for other carbon materials as well. The specific capacitance values of activated carbon in lithium-containing electrolytes reported by other authors range from 60 to 165 F g À1 [8,17,21,22,28,39]. For example, Krause et al [39] obtained a specific capacitance of approximately 110 F g À1 for their carbon black electrodes in a LIC with a LiFePO 4 positive electrode.…”
Section: Comparison Of the Different Lic Cell Typesmentioning
confidence: 96%
“…106,107,109 A LIC cell of hard carbon (HC)/1.3 mol L ─1 LiPF6/EC-DEC-PC/AC was reported to show high specific energy of 82 Wh kg ─1 at 2.4 C. Another LIC cell with 1.0 mol L ─1 LiPF6 in EC+DMC (1:1, v/v) exhibited the highest specific energy of 103.8 Wh kg ─1 and a good capacity retention of over 85 % after 10,000 cycles in a voltage range from 1.5 V up to 4.5 V. 110 Since the graphite negatrode did not initially contain Li, pre-lithiation of the graphite negatrode was a key aspect of this LIC. 111 It was also reported that capacity loss of the LICs during charge-discharge cycling was obviously reduced by addition of Li metal into the cell. 112,113 The highest potential of the AC electrode should be lower than 4.5 V vs Li + /Li, while the lowest potential of the HC/stabilized Li metal powder (SLMP) electrode should be greater than 0.1 V vs. Li + /Li.…”
Section: Supercapacitorsmentioning
confidence: 97%
“…Although many material combinations are possible for the assembly of LIC, the use of activated carbon positive electrode together with lithium intercalation negative electrode appear the most convenient till now [23][24][25]. In LIC, the negative electrode materials that can be doped with lithium ion typically include Li 4 Ti 5 O 12 [26], graphite [17,27], soft carbon [10,28], and hard carbon [29][30][31]. Among these materials, graphite was an attractive negative electrode material for LIC due to its high theoretical capacity, low and stable charge-discharge plateau, natural abundance and relative low cost.…”
Section: Introductionmentioning
confidence: 99%